Thermoelectric conversion material, thermoelectric conversion element, and thermoelectric conversion module
By incorporating specific noble gas additive elements in a semiconductor-based thermoelectric conversion material, the efficiency of thermoelectric energy conversion is enhanced through increased Seebeck coefficient and power factor.
Patent Information
- Application Number
- JP2021167520
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-12
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2041-10-12
AI Technical Summary
Existing thermoelectric conversion materials struggle to efficiently convert temperature differences into electricity due to limitations in the power factor (PF), which is influenced by the Seebeck coefficient and conductivity.
A thermoelectric conversion material comprising a semiconductor base material with an additive element, such as He, Ne, Ar, Kr, or Xe, at a content ratio of 0.01 at% to 2.0 at%, which increases the Seebeck coefficient while maintaining conductivity, thereby enhancing the power factor.
The proposed thermoelectric conversion material effectively increases the Seebeck coefficient and power factor, leading to improved efficiency in converting thermal energy into electricity.
Smart Images

Figure 0007649727000001 
Figure 0007649727000002 
Figure 0007649727000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a thermoelectric conversion material, a thermoelectric conversion element, and a thermoelectric conversion module. [Background technology]
[0002] A method for producing a thermoelectric conversion material that converts a temperature difference (thermal energy) into electricity has been disclosed (see, for example, Patent Document 1). According to Patent Document 1, the method is characterized by comprising the steps of putting two or more kinds of metal raw materials into a pulverizer, evacuating the inside of the pulverizer or replacing the inside of the pulverizer with an inert gas, pulverizing and mixing the metal raw materials while maintaining the metal raw materials at a temperature lower than their crystallization temperature to obtain an alloy powder, and compressing and molding the alloy powder, followed by heat treatment at a temperature lower than the crystallization temperature of the alloy powder. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 3-244167 Summary of the Invention [Problem to be solved by the invention]
[0004] Thermoelectric conversion materials are materials that convert temperature differences (thermal energy) into electricity. The power factor (hereinafter sometimes abbreviated as "PF"), which corresponds to the amount of power generated per unit temperature difference, is expressed by the following formula (1). In formula (1), S is the Seebeck coefficient, and σ is the electrical conductivity.
[0005] PF=S 2 ×σ (1)
[0006] In order to perform efficient thermoelectric conversion, it is important to increase the PF. If the PF can be increased, the efficiency of thermoelectric conversion can be improved.
[0007] Therefore, one of the objects is to provide a thermoelectric conversion material capable of improving the efficiency of thermoelectric conversion. [Means for solving the problem]
[0008] The thermoelectric conversion material according to the present disclosure includes a base material that is a semiconductor and an additive element whose content is 0.01 at% or more and 2.0 at% or less. The additive element includes at least one of He, Ne, Ar, Kr, and Xe. Effect of the Invention
[0009] The above thermoelectric conversion material can improve the efficiency of thermoelectric conversion. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic diagram showing the state of the structure of the thermoelectric conversion material in the first embodiment. [Diagram 2] FIG. 2 is a flowchart showing typical steps of a method for producing a thermoelectric conversion material in the first embodiment. [Diagram 3] FIG. 3 is a graph showing the relationship between the Ar concentration and the Seebeck coefficient in the thermoelectric conversion material of the first embodiment. [Figure 4] FIG. 4 is a graph showing the relationship between the Ar concentration and the electrical conductivity in the thermoelectric conversion material of the first embodiment. [Diagram 5] FIG. 5 is a graph showing the relationship between the Ar concentration and the PF in the thermoelectric conversion material of the first embodiment. [Figure 6] FIG. 6 is a graph showing the relationship between the Ar concentration and the PF in the thermoelectric conversion material according to the second embodiment. [Figure 7] FIG. 7 is a graph showing the relationship between the Ar concentration and the PF in the thermoelectric conversion material according to the third embodiment. [Figure 8] FIG. 8 is a schematic cross-sectional view showing the structure of the thermoelectric material element according to the first embodiment. [Figure 9] FIG. 9 is a diagram showing an example of the structure of a power generation module. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be described. The thermoelectric conversion material according to the present disclosure includes a base material that is a semiconductor and an additive element whose content is 0.01 at% or more and 2.0 at% or less. The additive element includes at least one of He, Ne, Ar, Kr, and Xe.
[0012] The present inventors focused on increasing the PF to improve the efficiency of thermoelectric conversion, and considered the need to increase the Seebeck coefficient while suppressing the decrease in electrical conductivity, leading to the construction of the thermoelectric conversion material according to the present disclosure. First, the present inventors considered that in order to increase the Seebeck coefficient, an additive element is inserted as an interstitial atom into the base material constituting the thermoelectric conversion material to generate point defects, and the potential disturbance created by this point defect generates an energy filtering effect to increase the Seebeck coefficient. Here, the present inventors also intensively studied the additive element used to generate point defects, and considered using an additive element containing at least one of He, Ne, Ar, Kr, and Xe, which does not bond or react with the elements constituting the base material, which is a semiconductor, and is unlikely to deteriorate the properties of the base material.
[0013] The inventors of the present application also conducted extensive research into the content of the additive element, and found that if the content of the additive element is too low, the Seebeck coefficient cannot be increased sufficiently, and if the content of the additive element is too high, the scattering of electrons due to the generated point defects becomes significant, resulting in a decrease in electrical conductivity and, conversely, a decrease in PF.
[0014] The thermoelectric conversion material of the present disclosure includes a base material that is a semiconductor and an additive element whose content is 0.01 at% or more and 2.0 at% or less, and the additive element includes at least one of He (helium), Ne (neon), Ar (argon), Kr (krypton) and Xe (xenon). With such a thermoelectric conversion material, it is possible to increase the Seebeck coefficient and increase the PF while suppressing the decrease in electrical conductivity. Therefore, such a thermoelectric conversion material can improve the efficiency of thermoelectric conversion.
[0015] In the thermoelectric conversion material, the base material may contain a nanocrystalline phase made of elements constituting a semiconductor. This can improve the efficiency of thermoelectric conversion. The nanocrystalline phase is a crystal phase in which the diameter of the smallest sphere containing a single crystal phase surrounded by crystal grain boundaries is 100 nm or less.
[0016] In the thermoelectric conversion material, the base material may contain an amorphous phase, which can further improve the efficiency of thermoelectric conversion.
[0017] In the thermoelectric conversion material, the base material may include a SiGe-based material. Such a base material is suitable for use as a thermoelectric conversion material. Here, the SiGe-based material refers to SiGe and a material in which at least one of Si and Ge in SiGe is partially replaced with another element, such as C, Sn, etc.
[0018] In the thermoelectric conversion material, the base material may contain a dopant, which can control the Fermi level and consequently improve the efficiency of thermoelectric conversion.
[0019] In the thermoelectric conversion material, the content of the additive element may be 0.03 at% or more and 1.0 at% or less. When this range of values is adopted as the content of the additive element, the Seebeck coefficient shows a particularly high value due to the energy filtering effect. Therefore, the efficiency of thermoelectric conversion can be improved.
[0020] The thermoelectric conversion element of the present disclosure includes a thermoelectric conversion material portion, a first electrode arranged in contact with the thermoelectric conversion material portion, and a second electrode arranged in contact with the thermoelectric conversion material portion and spaced apart from the first electrode. The material constituting the thermoelectric conversion material portion is the thermoelectric conversion material of the present disclosure, the composition of which is adjusted so that the conductivity type is p-type or n-type.
[0021] The thermoelectric conversion element of the present disclosure is a thermoelectric conversion material in which the material constituting the thermoelectric conversion material portion has a component composition adjusted so that the conductivity type is p-type or n-type, thereby improving the efficiency of the thermoelectric conversion. Therefore, according to the thermoelectric conversion element of the present disclosure, it is possible to provide a thermoelectric conversion element in which the efficiency of thermoelectric conversion is improved.
[0022] The thermoelectric conversion module of the present disclosure includes a plurality of the thermoelectric conversion elements. According to the thermoelectric conversion module of the present disclosure, by including a plurality of the thermoelectric conversion elements of the present disclosure that improve the efficiency of thermoelectric conversion, it is possible to obtain a thermoelectric conversion module that improves the efficiency of thermoelectric conversion.
[0023] [Details of the embodiment of the present disclosure] Next, an embodiment of the thermoelectric conversion material of the present disclosure will be described with reference to the drawings. In the following drawings, the same or corresponding parts are designated by the same reference characters, and the description thereof will not be repeated.
[0024] (Embodiment 1) The configuration of the thermoelectric conversion material according to the first embodiment of the present disclosure will be described. FIG. 1 is a schematic diagram showing the state of the structure of the thermoelectric conversion material according to the first embodiment. With reference to FIG. 1, the thermoelectric conversion material 11 according to the first embodiment of the present disclosure includes a base material 12 which is a semiconductor. The base material 12 which is a semiconductor is composed of, for example, a SiGe-based material. In this embodiment, the base material 12 which is a semiconductor is SiGe (silicon germanium). The base material 12 includes an amorphous phase 13 and a nanocrystalline phase 14. The nanocrystalline phase 14 is composed of elements which constitute a semiconductor. Specifically, the nanocrystalline phase 14 is SiGe. The nanocrystalline phase 14 is arranged in a moderately dispersed state in the amorphous phase 13.
[0025] The thermoelectric conversion material 11 includes an additive element. Although the additive element is not shown in FIG. 1, it is considered that the additive element is present, for example, near the interface between the nanocrystalline phase 14 and the amorphous phase 13 in the thermoelectric conversion material 11. The additive element includes at least one of He, Ne, Ar, Kr, and Xe. The additive element is an element belonging to an inert gas. In this embodiment, the additive element is Ar.
[0026] The content ratio of the additive element is 0.01 at% or more and 2.0 at% or less. Here, the content ratio of the additive element that is more than 0.1 at% can be measured, for example, by EDX (Energy Dispersive X-ray spectrometry). The EDX was measured by taking a TEM (Transmission Electron Microscope) image of a part of the thermoelectric conversion material 11. The TEM image was taken using JEM-2800 (manufactured by JEOL Ltd.), and the measurement conditions were an acceleration voltage of 200 kV, a probe size of 0.5 nm, and a CL aperture of 3. In addition, the condition for detecting atoms by EDX was used with EDX (manufactured by Thermo Fisher Scientific Co., Ltd.), and the measurement conditions were a spot size of 0.5 nm, a CL aperture of 3, an analysis mode of mapping, and an analysis time of 20 minutes. In addition, the content ratio of the additive element that is 0.1 at% or less can be measured, for example, by SIMS (Secondary Ion Mass Spectromrtry). As a specific measurement method, ADEPT-1010 manufactured by ULVAC, Inc. was used, and the ion source used in the measurement was CsR+ ions for the additive element R. For example, cesium argon ions CsAr+ were used in the measurement of the additive element Ar.
[0027] The thermoelectric conversion material 11 also contains a dopant. In this embodiment, the thermoelectric conversion material 11 contains P (phosphorus) as a dopant.
[0028] The thermoelectric conversion material 11 in the first embodiment can be manufactured, for example, by the following manufacturing method. FIG. 2 is a flow chart showing typical steps of the manufacturing method of the thermoelectric conversion material 11 in the first embodiment. Referring to FIG. 2, in the manufacturing method of the thermoelectric conversion material 11 in the first embodiment, a raw material introduction step is carried out as a step (S10). In this step (S10), first, weighed powders of Si, Ge and P are introduced into a grinding container together with milling balls. Then, an atmosphere replacement step is carried out as a step (S20). In this step (S20), the air in the grinding container is replaced with Ar gas. At this time, the pressure of the Ar gas is made higher than atmospheric pressure. Specifically, for example, the pressure of the Ar gas is set to 1.5 atm or more and 10.0 atm or less. It is considered that Ar can be introduced into the powder raw material by adjusting the pressure of the Ar gas in this way and carrying out the subsequent milling step. Thereafter, a milling step is carried out as a step (S30). In this step (S30), milling is carried out on the grinding container to make each raw material into a fine powder. At this time, it is believed that some of the Ar is also attached to the surface of the fine powder.
[0029] Next, a filling step is carried out as step (S40). In this step (S40), the obtained fine powder is filled into a prepared die. After that, a sintering step is carried out as step (S50). In this step, the fine powder filled into the die is heated to sinter the fine powder. In this embodiment, a sintered body is formed by a spark plasma sintering method. The temperature at this time can be, for example, 600°C. In this way, a thermoelectric conversion material is produced that is composed of a sintered body in which Ar as an additive element is contained in the sintered body and a nanocrystalline phase exists in an amorphous phase.
[0030] FIG. 3 is a graph showing the relationship between the Ar concentration and the Seebeck coefficient in the thermoelectric conversion material 11 of the first embodiment. In FIG. 3, the horizontal axis indicates the Ar concentration (at%), and the vertical axis indicates the Seebeck coefficient (μV / K). Here, the Seebeck coefficient and the electrical conductivity, which will be described later, were measured as follows. The electrical conductivity and the Seebeck coefficient were measured using a thermoelectric property measuring device (RZ2001i manufactured by Ozawa Scientific Co., Ltd.). The measurement method is as follows. First, the thermoelectric conversion material is fixed to a pair of quartz jigs so as to bridge the material, and the atmosphere is heated in a resistance heating furnace. One of the quartz jigs is made hollow, and nitrogen gas is flowed therein to cool the material, thereby cooling one end of the thermoelectric conversion material. This provides a temperature difference to the thermoelectric conversion material. For the thermoelectric conversion material, a platinum-platinum-rhodium thermocouple (R thermocouple) is used to measure the temperature difference between two points on the surface of the thermoelectric conversion material. By connecting a voltmeter to the thermocouple, the voltage generated by the temperature difference between the two points is measured. This makes it possible to measure the voltage generated in relation to the temperature difference, which makes it possible to estimate the Seebeck coefficient of the material. The resistance value is measured using the four-terminal method. That is, two electric wires are connected to the outside of the two platinum wires to which the voltmeter is connected. A current is passed through the wires, and the voltage drop is measured with the inner voltmeter. In this way, the resistance value of the thermoelectric conversion material is measured using the four-terminal method. The conductivity is derived from the measured resistance value.
[0031] 3, it can be seen that the Seebeck coefficient increases as the Ar content increases, i.e., as the Ar concentration increases. It can also be seen that the rate of increase in the Seebeck coefficient in the high Ar concentration region is lower than the rate of increase in the Seebeck coefficient in the low Ar concentration region. It can also be seen that when the Ar concentration is 0.01 at% or more, the Seebeck coefficient increases by more than about 250 μV / K. It can also be seen that when the Ar concentration is 1.0 at% or more, the Seebeck coefficient becomes almost constant.
[0032] Fig. 4 is a graph showing the relationship between the Ar concentration and the electrical conductivity in the thermoelectric conversion material 11 of the first embodiment. In Fig. 4, the horizontal axis shows the Ar concentration (at%), and the vertical axis shows the electrical conductivity (S / m). The electrical conductivity was measured as described above.
[0033] 4, in the region where the Ar content is relatively low, the electrical conductivity is almost constant, but as the Ar content increases, specifically, the Ar concentration increases beyond 0.02 at%, the electrical conductivity decreases, and when the Ar concentration increases beyond 2.0 at%, the electrical conductivity decreases significantly, becoming smaller than 25,000 S / m.
[0034] 5 is a graph showing the relationship between the Ar concentration and the PF in the thermoelectric conversion material 11 of the first embodiment. In FIG. 5, the horizontal axis shows the Ar concentration (at %), and the vertical axis shows the PF (μW / cmK 2 PF is a value calculated based on the values of the graphs shown in Figs. 3 and 4.
[0035] With reference to FIG. 5, for PF, when the content of Ar is 0.01 at % or more and 2.0 at % or less, the maximum value of 20 μW / cmK 2 Thus, it is possible to improve the efficiency of thermoelectric conversion.
[0036] As described above, the Seebeck coefficient can be increased and the PF can be increased while suppressing a decrease in electrical conductivity, according to the thermoelectric conversion material 11. Therefore, the thermoelectric conversion material 11 can improve the efficiency of thermoelectric conversion.
[0037] In the thermoelectric conversion material 11, the content of the additive element may be 0.03 at% or more and 1.0 at% or less. When this range of values is adopted as the content of the additive element, the Seebeck coefficient shows a particularly high value due to the energy filtering effect. Therefore, the efficiency of thermoelectric conversion can be improved.
[0038] In this embodiment, the base material 12 includes a nanocrystalline phase 14 made of elements constituting a semiconductor. This can further improve the efficiency of thermoelectric conversion. The improvement in the efficiency of thermoelectric conversion due to the base material 12 including the nanocrystalline phase 14 is considered to be, for example, as follows. That is, by including the nanocrystalline phase 14 made of elements constituting a semiconductor, the added element is highly concentrated at the grain boundaries of the nanocrystalline phase 14. This makes it easier to generate a nanoscale distribution in the added element, and it is considered that a greater energy filtering effect can be obtained.
[0039] In addition, in this embodiment, the base material 12 includes an amorphous phase 13. Therefore, the efficiency of thermoelectric conversion can be further improved. The reason for the improvement in the efficiency of thermoelectric conversion due to the base material 12 including the amorphous phase 13 is considered to be as follows. That is, it is considered that the base material 12 including the amorphous phase 13 increases the local disturbance of the potential due to the point defects of the added element, and thus a greater energy filtering effect can be obtained.
[0040] In the present embodiment, the base material 12 includes a SiGe-based material, which is suitable for use as a thermoelectric conversion material.
[0041] In this embodiment, the base material 12 contains P as a dopant. Therefore, the Fermi level can be controlled, and as a result, the efficiency of thermoelectric conversion can be improved. Other elements used as dopants include As (arsenic), Sb (antimony), N (nitrogen), B (boron), Al (aluminum), and Ga (gallium). The dopant may contain at least one of P, As, Sb, N, B, Al, and Ga. An appropriate dopant is selected depending on the desired properties of the thermoelectric conversion material and the elements constituting the base material. The thermoelectric conversion material 11 of the present disclosure may be configured not to contain a dopant.
[0042] In the above embodiment, the sintering step S50 in the manufacturing method of the thermoelectric conversion material 11 is not limited to spark plasma sintering, and may be performed by, for example, hot pressing. In the above embodiment, the atmosphere replacement step S20 is performed using Ar gas and N 2 The atmosphere may be replaced with a mixed gas obtained by mixing Ar gas with Ar gas. In this case, the partial pressure in the mixed gas may be controlled to adjust the pressure of the Ar gas. In addition, in the above embodiment, Ar is used as the additive element, but the additive element is not limited to this, and may be configured to include at least one of He, Ne, Ar, Kr, and Xe.
[0043] (Embodiment 2) Next, a second embodiment, which is another embodiment, will be described. In the thermoelectric conversion material of the second embodiment, the base material is SiGe and the dopant is P. That is, the base material and the dopant are the same as those of the thermoelectric conversion material of the first embodiment. And, unlike the thermoelectric conversion material of the first embodiment, the thermoelectric conversion material of the second embodiment employs Kr as an additive element.
[0044] 6 is a graph showing the relationship between the Kr concentration and the PF in the thermoelectric conversion material of the second embodiment. In FIG. 6, the horizontal axis shows the Kr concentration (at%), and the vertical axis shows the PF (μW / cmK 2 ) is shown.
[0045] With reference to FIG. 6, when the content of Kr is 0.023 at%, the value of PF is 27 μW / cmK. 2 As for PF, when the Kr content is 1.0 at%, the PF value is 30 μW / cmK. 2 , which shows a large value. It can be seen that, in the thermoelectric conversion material of the second embodiment, when the content ratio of Kr is 0.01 at% or more and 2.0 at% or less, a high value is realized for PF. Therefore, it is possible to improve the efficiency of thermoelectric conversion.
[0046] (Embodiment 3) Next, a third embodiment, which is yet another embodiment, will be described. In the thermoelectric conversion material of the third embodiment, the base material is Cu. 2 The thermoelectric conversion material of the third embodiment is composed of Ar and does not contain any dopant. In other words, the base material is different from that of the thermoelectric conversion material of the first embodiment. Unlike the thermoelectric conversion material of the first embodiment, the thermoelectric conversion material of the third embodiment does not contain any dopant. The thermoelectric conversion material of the third embodiment employs Ar as an additive element, as in the case of the thermoelectric conversion material of the first embodiment. Note that in this embodiment, the base material is Cu. 2 Se-based materials are also acceptable. Cu 2 Se-based materials are Cu 2 Se, and Cu 2 It refers to a material in which at least one of Cu (copper) and Se (selenium) in Se is partially replaced by another element.
[0047] 7 is a graph showing the relationship between the Ar concentration and the PF in the thermoelectric conversion material of the third embodiment. In FIG. 7, the horizontal axis shows the Ar concentration (at%), and the vertical axis shows the PF (μW / cmK 2 ) is shown.
[0048] With reference to FIG. 7, when the content of Ar is 0.08 at%, the value of PF is 140 μW / cmK. 2 As for PF, when the Ar content is 0.6 at%, the PF value is 136 μW / cmK. 2 , which shows a large value. It can be seen that, in the thermoelectric conversion material of the third embodiment, when the content ratio of Ar is 0.01 at% or more and 2.0 at% or less, a high value is realized for PF. Therefore, it is possible to improve the efficiency of thermoelectric conversion.
[0049] (Embodiment 4) Next, a power generating element will be described as one embodiment of a thermoelectric conversion element using the thermoelectric conversion material 11 in the first embodiment.
[0050] Fig. 8 is a schematic cross-sectional view showing the structure of a thermoelectric material element according to embodiment 1. Note that, in order to facilitate understanding, some of the hatching showing the cross section has been omitted in Fig. 8.
[0051] 8, a π-type thermoelectric conversion element 21 includes a p-type thermoelectric conversion material section 22, an n-type thermoelectric conversion material section 23, a high-temperature side electrode 24, a first low-temperature side electrode 25, a second low-temperature side electrode 26, and wiring 27. The high-temperature side electrode 24 is a first electrode arranged in contact with the thermoelectric conversion material sections 22, 23. The first low-temperature side electrode 25 is a second electrode arranged in contact with the thermoelectric conversion material section 22 and spaced apart from the high-temperature side electrode 24. The second low-temperature side electrode 26 is a second electrode arranged in contact with the thermoelectric conversion material section 23 and spaced apart from the high-temperature side electrode 24.
[0052] The material constituting the p-type thermoelectric conversion material section 22 is, for example, the thermoelectric conversion material of the first embodiment whose composition has been adjusted so that the conductivity type is p-type. The material constituting the n-type thermoelectric conversion material section 23 is, for example, the thermoelectric conversion material of the first embodiment whose composition has been adjusted so that the conductivity type is n-type.
[0053] The p-type thermoelectric conversion material section 22 and the n-type thermoelectric conversion material section 23 are arranged side by side with a gap therebetween. The high-temperature side electrode 24 is arranged so as to extend from one end 31 of the p-type thermoelectric conversion material section 22 to one end 32 of the n-type thermoelectric conversion material section 23. The high-temperature side electrode 24 is arranged so as to contact both one end 31 of the p-type thermoelectric conversion material section 22 and one end 32 of the n-type thermoelectric conversion material section 23. The high-temperature side electrode 24 is arranged so as to connect one end 31 of the p-type thermoelectric conversion material section 22 and one end 32 of the n-type thermoelectric conversion material section 23. The high-temperature side electrode 24 is made of a conductive material, for example, a metal. The high-temperature side electrode 24 is in ohmic contact with the p-type thermoelectric conversion material section 22 and the n-type thermoelectric conversion material section 23.
[0054] The thermoelectric conversion material portion 22 or the thermoelectric conversion material portion 23 is preferably a p-type or n-type, but either one may be a metal conductor.
[0055] The first low-temperature side electrode 25 is arranged in contact with the other end 33 of the p-type thermoelectric conversion material part 22. The first low-temperature side electrode 25 is arranged away from the high-temperature side electrode 24. The first low-temperature side electrode 25 is made of a conductive material, for example, a metal. The first low-temperature side electrode 25 is in ohmic contact with the p-type thermoelectric conversion material part 22.
[0056] The second low-temperature side electrode 26 is arranged in contact with the other end 34 of the n-type thermoelectric conversion material part 23. The second low-temperature side electrode 26 is arranged away from the high-temperature side electrode 24 and the first low-temperature side electrode 25. The second low-temperature side electrode 26 is made of a conductive material, for example, a metal. The second low-temperature side electrode 26 is in ohmic contact with the n-type thermoelectric conversion material part 23.
[0057] The wiring 27 is made of a conductor such as a metal, etc. The wiring 27 electrically connects the first low-temperature side electrode 25 and the second low-temperature side electrode 26.
[0058] In the π-type thermoelectric conversion element 21, when a temperature difference is formed such that, for example, one end 31 of the p-type thermoelectric conversion material part 22 and one end 32 of the n-type thermoelectric conversion material part 23 are at high temperature, and the other end 33 of the p-type thermoelectric conversion material part 22 and the other end 34 of the n-type thermoelectric conversion material part 23 are at low temperature, p-type carriers (holes) move from one end 31 side to the other end 33 side in the p-type thermoelectric conversion material part 22. At this time, n-type carriers (electrons) move from one end 32 side to the other end 34 side in the n-type thermoelectric conversion material part 23. As a result, a current flows in the wiring 27 in the direction of the arrow I. In this way, in the π-type thermoelectric conversion element 21, power generation is achieved by thermoelectric conversion using a temperature difference. That is, the π-type thermoelectric conversion element 21 is a power generation element.
[0059] The thermoelectric conversion material 11 of the first embodiment is used as a material for forming the p-type thermoelectric conversion material section 22 and the n-type thermoelectric conversion material section 23. As a result, the π-type thermoelectric conversion element 21 is a highly efficient power generating element.
[0060] In the above embodiment, a π-type thermoelectric conversion element has been described as an example of the thermoelectric conversion element of the present disclosure, but the thermoelectric conversion element of the present disclosure is not limited to this. The thermoelectric conversion element of the present disclosure may be a thermoelectric conversion element having another structure, such as an I-type (uni-leg type) thermoelectric conversion element.
[0061] In the above embodiment, the thermoelectric conversion material 11 of the first embodiment is adopted as the material constituting the p-type thermoelectric conversion material section 22 and the n-type thermoelectric conversion material section 23, but this is not limited thereto. That is, the thermoelectric conversion material of the second embodiment or the thermoelectric conversion material of the third embodiment may be adopted as the material constituting the p-type thermoelectric conversion material section 22 and the n-type thermoelectric conversion material section 23. The material constituting the p-type thermoelectric conversion material section 22 and the material constituting the n-type thermoelectric conversion material section 23 may be different materials.
[0062] (Embodiment 5) A power generation module serving as a thermoelectric conversion module can be obtained by electrically connecting a plurality of the π-type thermoelectric conversion elements 21. The power generation module 41, which is a thermoelectric conversion module of the present embodiment, has a structure in which a plurality of π-type thermoelectric conversion elements 21 are connected in series.
[0063] FIG. 9 is a diagram showing an example of the structure of a power generation module. Referring to FIG. 9, a power generation module 41 of the present embodiment includes a plurality of p-type thermoelectric conversion material parts 22, a plurality of n-type thermoelectric conversion material parts 23, low-temperature side electrodes 25 and 26 corresponding to the first low-temperature side electrode 25 and the second low-temperature side electrode 26, a high-temperature side electrode 24, a low-temperature side insulator substrate 28, and a high-temperature side insulator substrate 29. The low-temperature side insulator substrate 28 and the high-temperature side insulator substrate 29 are made of ceramic such as alumina. The p-type thermoelectric conversion material parts 22 and the n-type thermoelectric conversion material parts 23 are arranged alternately. The low-temperature side electrodes 25 and 26 are arranged in contact with the p-type thermoelectric conversion material parts 22 and the n-type thermoelectric conversion material parts 23 in the same manner as the above-mentioned π-type thermoelectric conversion element 21. The high-temperature side electrode 24 is arranged in contact with the p-type thermoelectric conversion material parts 22 and the n-type thermoelectric conversion material parts 23 in the same manner as the above-mentioned π-type thermoelectric conversion element 21. The p-type thermoelectric conversion material section 22 is connected to an adjacent n-type thermoelectric conversion material section 23 on one side by a common high-temperature side electrode 24. In addition, the p-type thermoelectric conversion material section 22 is connected to an adjacent n-type thermoelectric conversion material section 23 on a side different from the one side by common low-temperature side electrodes 25, 26. In this manner, all of the p-type thermoelectric conversion material sections 22 and n-type thermoelectric conversion material sections 23 are connected in series.
[0064] The low-temperature-side insulator substrate 28 is disposed on the main surface side opposite to the side in contact with the p-type thermoelectric conversion material section 22 and the n-type thermoelectric conversion material section 23 of the plate-shaped low-temperature-side electrodes 25, 26. One low-temperature-side insulator substrate 28 is disposed for each of the plurality (all) of low-temperature-side electrodes 25, 26. The high-temperature-side insulator substrate 29 is disposed on the side opposite to the side in contact with the p-type thermoelectric conversion material section 22 and the n-type thermoelectric conversion material section 23 of the plate-shaped high-temperature-side electrode 24. One high-temperature-side insulator substrate 29 is disposed for each of the plurality (all) of high-temperature-side electrodes 24.
[0065] Wiring 42, 43 is connected to high-temperature side electrode 24 or low-temperature side electrodes 25, 26 in contact with p-type thermoelectric conversion material section 22 or n-type thermoelectric conversion material section 23 located at both ends of p-type thermoelectric conversion material section 22 and n-type thermoelectric conversion material section 23 connected in series. When a temperature difference is formed such that high-temperature side insulator substrate 29 side is high temperature and low-temperature side insulator substrate 28 side is low temperature, current flows in the direction of arrow I through p-type thermoelectric conversion material section 22 and n-type thermoelectric conversion material section 23 connected in series, similar to the case of π-type thermoelectric conversion element 21. In this way, power generation is achieved in power generation module 41 by thermoelectric conversion utilizing the temperature difference.
[0066] Such a power generation module 41 includes a plurality of thermoelectric conversion elements 21 according to the present disclosure, which have improved thermoelectric conversion efficiency, and thus can achieve high thermoelectric conversion efficiency.
[0067] It should be understood that the embodiments disclosed herein are illustrative in all respects and are not limiting in any respect. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. [Industrial Applicability]
[0068] The thermoelectric conversion material, thermoelectric conversion element, and thermoelectric conversion module of the present disclosure can be particularly advantageously applied in cases where improved thermoelectric conversion efficiency is required. [Explanation of symbols]
[0069] 11 Thermoelectric materials 12 Base Material 13 Amorphous phase 14 Nanocrystalline phase 21 Thermoelectric conversion element 22,23 Thermoelectric Materials Department 24 High temperature side electrode 25,26 Low temperature electrode 27,42,43 Wiring 28 Low temperature side insulator substrate 29 High temperature side insulator substrate 31, 32, 33, 34 End 41 Power generation module I Arrow
Claims
1. a base material that is a semiconductor; An additive element having a content of 0.01 at% or more and 2.0 at% or less, The additive element includes at least one of He, Ne, Ar, Kr, and Xe, The base material is An amorphous phase; A nanocrystalline phase that is arranged in a dispersed state in the amorphous phase and is made of elements that constitute the semiconductor, The thermoelectric conversion material, wherein the base material is SiGe.
2. A base material which is a semiconductor; An additive element having a content of 0.01 at% or more and 2.0 at% or less, The additive element includes at least one of He, Ne, Ar, Kr, and Xe, The base material is An amorphous phase; A nanocrystalline phase that is arranged in a dispersed state in the amorphous phase and is made of elements that constitute the semiconductor, The thermoelectric conversion material, wherein the base material is Cu 2 Se.
3. The thermoelectric conversion material according to claim 1 or 2, wherein the thermoelectric conversion material contains a dopant.
4. The thermoelectric conversion material according to claim 1 , wherein a content ratio of the additive element is 0.03 at % or more and 1.0 at % or less.
5. Thermoelectric Materials Department; a first electrode disposed in contact with the thermoelectric conversion material portion; a second electrode in contact with the thermoelectric conversion material portion and disposed apart from the first electrode; A thermoelectric conversion element, comprising the thermoelectric conversion material according to claim 1 , the thermoelectric conversion material portion having a component composition adjusted to have a conductivity type of p-type or n-type.
6. A thermoelectric conversion module comprising a plurality of thermoelectric conversion elements as described in claim 5.
Citation Information
Patent Citations
Manufacture of thermoelectric conversion element material
JP1991244167A
Apparatus for production of thermoelectric conversion semiconductor material
JP1994205999A
Manufacture of thermoelectric semiconductor
JP1999274583A
Titanium nitride thin-film thermoelectric semiconductor, method for manufacturing the same, and thermoelectric power generation element
JP2016181571A
Nanostructured copper-selenide with high thermoelectric figure-of-merit and process for the preparation thereof
US20160225972A1